(untitled) (Research, Society and Development, 2021)
Visceral Leishmania is the clinical form of leishmaniasis that is most associated with HIV/AIDS. The co-infection Leishmania sp/HIV has been considered as an emerging disease in several regions of the world due to the geographical overlap of the two infections, as a consequence of the urbanization of leishmaniasis and the ruralization of HIV infection. The present work aims to study the epidemiological profile of reported cases of co-infection of visceral leishmaniasis and human immunodeficiency virus in the years 2010 to 2019 in São Luis, Maranhão State. All data were collected in November 2020 through the Acute Notification Information System (SINAN) made available on the website of the Department of Informatics of the Unified Health System (DATASUS), taking into account the variables chosen as age, education, gender, ethnicity and diagnosis. The Acute Notification Information System (SINAN) between the years 2010 and 2019 were notified 1994 cases of visceral leishmaniasis in São Luis Maranhão, of which 321 had co-infection with HIV. We can observe that between 2010 and 2019 a percentage of 83.80% reported were male, between the ages of 40-59, especially individuals of black race / color with low education. Based on the analysis we can observe that the most affected population are vulnerable people with a reduced level of education which makes them more susceptible, and action is needed to raise health awareness aimed at such population in order to direct the control of the disease and make the control more effective.